Penggunaan Artificial Intelligence dalam Optimalisasi Pengawasan dan Perlindungan Hukum bagi Anak dalam Sistem Peradilan Pidana - Naufal Kurnia Ramadhani; Muhammad Rizal Rustam (LPPM Iblam School of Law, 2025)
This study examines the legal, social, and psychological impacts of postponing the execution of death sentences in Indonesia's new Criminal Code (KUHP). The 10-year probation period for death row inmates creates legal uncertainty regarding the timing of executions and the potential for changes in sentencing. Using qualitative methods and a normative legal approach, this study analyses the relevant regulations and interpretations of legal norms through a literature review. The results show that postponing executions exacerbates psychological pressure on convicts, such as severe stress and mental disorders, and undermines public confidence in the fairness of the criminal justice system. In addition, there is a risk of human rights violations due to unclear procedures and long waiting periods. From a legal perspective, this situation indicates the need for more explicit and consistent regulations to ensure legal certainty and substantive justice. Therefore, reforming the execution time limit and oversight mechanisms is considered important to improve the effectiveness and integrity of Indonesia's criminal justice system.